Attitudes, beliefs and responsibility for heritage language maintenance in the UK. Issue 1 (1st January 2020) - Weekly, Robert
ABSTRACT: In this paper, I draw on interview data with multilingual British South-Asian English language teachers to examine their language attitudes and beliefs about the responsibility for heritage language maintenance in the UK. While all the participants feel that it is important for heritage languages to be maintained, differences emerged with respect to the level of responsibility that the mainstream education sector has in this maintenance. Irrespective of the role of local education authorities, the primary responsibility is seen as being with parents and families. This paper argues that this stems from several factors including the lack of heritage language support for families and the ideological construction of heritage languages as being primarily a community and parental responsibility. In addition, the strong links between heritage languages and culture, religion and ethnicity contribute to characterise heritage languages as being outside children's formal education.